2021
DOI: 10.3390/curroncol28010035
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Radiotherapy on the Incidence of Secondary Malignancies: A Pan-Cancer Study in the US SEER Cancer Registries

Abstract: The population of cancer patients with second primary malignancies (SPMs) is rapidly growing. The relationship between radiotherapy and SPMs for some types of tumors is unknown or debated. In this study, we identify 24 types of first primary malignancies (FPMs) between 2004 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) database. Patients in the radiotherapy group were matched to those in the no radiotherapy group with a matching ratio of 1:1. After propensity-score matching (PSM), addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The tumor initially exhibited a partial response to chemotherapy with subsequent complete response to chemoradiation. Radiation-induced secondary malignancies (RISMs) are well recognized complications of oncological intervention (24)(25)(26). The defining criteria for RISMs are that the tumor occurs within the previously irradiated field, the amount of radiation is significant, there is a latency period of at least 3 yr and 375 CERVICAL SMALL CELL VARIANT OF PARAGANGLIOMA the histology is different from the primary tumor (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The tumor initially exhibited a partial response to chemotherapy with subsequent complete response to chemoradiation. Radiation-induced secondary malignancies (RISMs) are well recognized complications of oncological intervention (24)(25)(26). The defining criteria for RISMs are that the tumor occurs within the previously irradiated field, the amount of radiation is significant, there is a latency period of at least 3 yr and 375 CERVICAL SMALL CELL VARIANT OF PARAGANGLIOMA the histology is different from the primary tumor (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [13] found that chemotherapy was not an important factor in survival, but patients with hormone receptor HR-positive high-risk breast cancer may benefit from chemotherapy. Li et al [14] noted that the effect of radiotherapy on secondary malignancy incidence was different in different types of cancers with different effects. The factors affecting the survival of breast cancer patients are numerous and complex, and the results of the above studies can serve as an important basis for the initial selection of influencing factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the classification principles of the US Census Bureau, 18 cancer registries were categorized into 4 regions, namely West, Northeast, North central, and South. [13] The primary sites included six groups, namely superior wall of the nasopharynx, posterior wall of the nasopharynx, lateral wall of the nasopharynx, anterior wall of the nasopharynx, overlapping lesion of the nasopharynx, and nasopharynx. Patients were also categorized based on whether they underwent surgery and radiotherapy.…”
Section: Study Variables and Endpointsmentioning
confidence: 99%